Utilization of MCH handbooks and attitudes of pregnant women regarding pregnancy and childbirth complications - Dian Irawati; Agustin Dwi Syalfina (Universitas Airlangga, 2019)
Objectives: Maternal Mortality Rate (MMR) is closely related to maternal care. MMR in Indonesia based on the 2015 IDHS is 359 per 100,000 live births. By increasing the utilization of MCH handbooks, MMR would be decline. Therefore, this research investigated the relationship between of the utilization of MCH handbooks and attitudes pregnant women regarding pregnancy and childbirth complications.Materials and Methods: We conducted a cross sectional research with 54 pregnant women during March - June 2018 at the Sooko Health Center, Mojokerto. The independent variable was the utilization of MCH handbooks and the dependent variable was the attitude of pregnan women regarding pregnancy and childbirth complications. Data analysis included descriptive and bivariate analysis.Results: The results showed that 79.6% of respondents used the MCH handbook well. The results of the chi square analysis test showed a p value of 0.027 (<0.05).Conclusion: MCH handbook utilization effected the attitude of pregnant women regarding the complication of pregnancy and childbirth. Pregnant women who read and utilize MCH handbook would be have better alertness about the risk of complication so they would make the right decision for their pregnancy.